Electrospinning of Polyacrylonitrile Nanofibers and Simulation of Electric Field via Finite Element method - Hadi Samadian (Nanomedicine Research Journal, 2017)
Objective(s): Since the electric field is the main driving force in electrospinning systems, the modeling and analysis of electric field distribution are critical to the nanofibers production. The aim of this study was modeling of the electric field and investigating the various parameters on polyacrylonitrile (PAN) nanofibers morphology and diameter. Methods: The electric field profile at the nozzle and electrospinning zone was evaluated by Finite Element Method. The morphology and diameter of nanofibers were examined by Scanning electron microscopy (SEM). Results: The results of the electric field analysis indicated that the electric field was concentrated at the tip of the nozzle. Moreover, in the spinning direction, the electric field was concentrated at the surface of the spinneret and decayed rapidly toward the surface of the collector. Increasing polymer solution concentration from 7 to 11wt.% led to increasing nanofibers diameter form 77.76 ± 19.44 to 202.42 ± 36.85. Conclusions: Base on our results, it could be concluded that concentration of the electric field at the tip of the nozzle is high and initiates jet and nanofibers formation. PAN nanofibers can be transformed to carbon nanofibers which have various applications in biomedicine.